Mobile Phone Innovation and Technology-driven Exports in Sub-Saharan Africa - Simplice Asongu (African Governance and Development Institute (AGDI), 2017)
The study investigates how education, scientific output and the internet complement mobile phone penetration to affect technology commodity exports in Sub-Saharan Africa for the period 2000-2012. The empirical evidence is based on Generalised Method of Moments. The following main findings are established. First, the internet complements the mobile phone to boost technology goods exports. Second, the internet also complements the mobile phone to boost technology service exports. Third, positive marginal effects are apparent in the roles of educational quality and scientific output on technology goods exports and technology service exports respectively while negative marginal impacts are apparent in the roles of scientific output and educational quality on technology goods exports and technology service exports respectively. Practical and theoretical implications are discussed.
Keywords: L59; L98; O10; O30; O55; 330; Technology exports; Knowledge Economy; Development; Africa